Private education: between neostatism and civil society (Cultura Económica, 2018)
In this essay, the autor raises the issue of relations between the State and civil society schools. In 1993 the Federal Education Law established that public and private schools equally contribute to society’s common good. However, in recent years this idea has led to the creation of a project for the nationalization of private education Torrendell reports because if applied it would erode civil society’s participation on education. Given this, the valuable role of private schools that enriches our society with its democratic pluralism must be recognized.
Keywords: EDUCATION; FEDERAL EDUCATION LAW; NATIONAL EDUCATION LAW; STATISM; CIVIL SOCIETY